Analyzing the communication patterns of different teammate types in a software engineering course project - Luther, Yanye, author; Nielsen, Lindsey, author; Cadman, Logan, author; Moraes, Marcia, author; Ghosh, Sudipto, author; Trinkenreich, Bianca, author; ACM, publisher (Colorado State University. Libraries, 2025)
Effective communication is vital for the success of professional software engineering (SE) teams. As SE courses teach essential industry skills like teamwork and collaboration, ensuring effective communication becomes important in student projects. However, poor engagement from team members can lead to conflicts, uneven workloads, and diminished learning experiences. Teammate types such as Couch Potatoes, who contribute minimally, and Hitchhikers, who rely on others while taking credit, exacerbate these issues. In contrast, Lone Wolves work independently, potentially isolating themselves, while Good Teammates actively collaborate and contribute fairly, driving team success. In this study, we aimed to investigate the communication patterns of teammate types such as Couch Potato, Hitchhiker, Lone Wolf, or Good Teammate during a SE testing course. We applied Ordered Network Analysis (ONA) to the conversational data of the teams to examine the distinct communication patterns of students whose contributions were either perceived positively (e.g., Good Teammates) or negatively (e.g., Couch Potato, Hitchhiker, Lone Wolf) by their peers. The findings reveal distinct communication behaviors across teammate types. While Good Teammates and Couch Potatoes discussed similar content, Good Teammates communicated more frequently and consistently throughout the project. Lone Wolves seldom engaged in pleasantries, reflecting a task-focused approach, whereas Hitchhikers rarely contributed substantively to technical discussions, such as pull requests, often interacted through pleasantries. These patterns emphasize the need for early interventions and communication planning to promote accountability balance and effective student collaboration during class projects.
Keywords: teamwork; communication; ordered network analysis